2019
DOI: 10.1109/access.2019.2918274
|View full text |Cite
|
Sign up to set email alerts
|

Bird Image Retrieval and Recognition Using a Deep Learning Platform

Abstract: Birdwatching is a common hobby but to identify their species requires the assistance of bird books. To provide birdwatchers a handy tool to admire the beauty of birds, we developed a deep learning platform to assist users in recognizing 27 species of birds endemic to Taiwan using a mobile app named the Internet of Birds (IoB). Bird images were learned by a convolutional neural network (CNN) to localize prominent features in the images. First, we established and generated a bounded region of interest to refine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…2), which makes imbalance learning worth being investigated. Previously, image data has been investigated for recognizing bird species [12], it it worthwhile fusing both audio and image data for classifying bird species. Another research direction is to build an efficient classification framework for recognizing bird species by intelligently fusing CNN models.…”
Section: Discussionmentioning
confidence: 99%
“…2), which makes imbalance learning worth being investigated. Previously, image data has been investigated for recognizing bird species [12], it it worthwhile fusing both audio and image data for classifying bird species. Another research direction is to build an efficient classification framework for recognizing bird species by intelligently fusing CNN models.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been attempts to apply identification methods other than by Neural Network, such as Haar Feature Based Cascade Classifier [48], which could give a better individual detection performance in comparison to CNN, but does not perform as well when tasks are conducted on many features [42]. Another method is the Long Short-Term Memory (LSTM) [45], which gives a better performance in bird identification near the moving blades of wind turbines.…”
Section: Identification Algorithmsmentioning
confidence: 99%
“…Nevertheless, identification of small birds with CNN-LSTM still requires improvement. Dense CNN [48] reported good identification performance with additional skip connections [46,53], which improve feature extraction. After 100 epochs, CNN with skip connections reach near 99% identification accuracy, when the same CNN architecture without skip connections reaches 89%.…”
Section: Identification Algorithmsmentioning
confidence: 99%
“…Whereas the motion detection algorithms allow the reduction of the computational complexity of the safety system [ 50 ], the application of AI methods allows bird identification [ 48 , 49 ] and the reduction of false positive rates [ 10 ]. From the AI based solutions, the Convolutional Neural Networks (CNNs) [ 51 , 52 , 53 ] outperform other methods, for instance the Haar feature based cascade classifier [ 45 , 54 ] or Long Short-Term Memory (LSTM) [ 48 ]. The most recent studies reported that dense CNN [ 54 ] shows good feature extraction capabilities allowing for bird identification [ 49 , 55 ], and after 100 epochs, the system reaches near 99% accuracy.…”
Section: Background and Related Workmentioning
confidence: 99%
“…From the AI based solutions, the Convolutional Neural Networks (CNNs) [ 51 , 52 , 53 ] outperform other methods, for instance the Haar feature based cascade classifier [ 45 , 54 ] or Long Short-Term Memory (LSTM) [ 48 ]. The most recent studies reported that dense CNN [ 54 ] shows good feature extraction capabilities allowing for bird identification [ 49 , 55 ], and after 100 epochs, the system reaches near 99% accuracy. Other CNNs, implemented in distributed computing and IoT paradigms, allow the system to ensure 99.8% precision with 99.0% recall in bird identification with real-time performance [ 10 ].…”
Section: Background and Related Workmentioning
confidence: 99%